Development of Analogy-Based Material Physics Module to Provide Analogy Ability of Physics Teachers Candidates (Department of Physics, Faculty of Mathematics and Natural Sciences, 2020)
It is known that the 'electronic structure of atoms' in material physics is microscopic. This atomic structure has an abstract and complicated concept, therefore good analogy skills are needed to study comprehensively. This research develops a free analogy-based material physics module to supply analogy skills to prospective physics teacher students. Module development uses the 4D model namely Define, Design, Development and Disseminate. The feasibility aspects are required based on the presentation, content, and grammar. Data obtained from expert assessment and trials using questionnaires, interviews, and tests. Increased student analogy skills were analyzed using normalized N-gain. The results obtained are: (1) the characteristics of the module that has learning steps such as teaching with analogy models, namely: introducing the concept of targets, reviewing the concept of analogies, identifying the relevant nature of targets and analogies, mapping analogies with targets, identifying analogies that are not relevant to targets, and make conclusions, (2) module quality on atomic electronic structure material developed is categorized as feasible, (3) modules are proven to increase mastery of the concept of atomic electronic structure (N-gain = 54%) and analytical skills prospective teachers physics (N-gain = 56%). The development of physics modules based on free analogies can be applied to other learning, such as biology, chemistry, and mathematics to explain abstract material.